Quantifying the antiviral effect of APOBEC3 on HIV-1 infection in humanized mouse model. (7th August 2020) - Kurusu, Tatsuya; Kim, Kwang Su; Koizumi, Yoshiki; Nakaoka, Shinji; Ejima, Keisuke; Misawa, Naoko; Koyanagi, Yoshio; Sato, Kei; Iwami, Shingo
Highlights: Modeling HIV-1 infection considering the antiviral effect of APOBEC3 proteins. Quantifying antiviral activity of APOBEC3F and APOBEC3G in vivo . APOBEC3G markedly and robustly restricted the initial stages of HIV-1 growth in vivo . Abstract: APOBEC3 proteins inhibit human immunodeficiency virus (HIV)-1 infection by independently impairing viral reverse transcription and inducing G-to-A mutations in viral DNA. An HIV-1-encoded protein, viral infectivity factor (Vif), can counteract these antiviral activities of APOBEC3 proteins. Although previous studies using in vitro cell culture systems have revealed the molecular mechanisms of the antiviral action of APOBEC3 proteins and their antagonism by Vif, it remains unclear how APOBEC3 proteins affect the kinetics of HIV-1 replication in vivo . Here we quantified the time-series of viral load datasets from humanized mice infected with HIV-1 variants in the presence of APOBEC3F, APOBEC3G, or both APOBEC3F/G using a simple mathematical model that accounted for inter-individual variability. Through experimental and mathematical investigation, we formulated and calculated the total antiviral activity of APOBEC3F and APOBEC3G based on the estimated initial growth rates of viral loads in vivo . Interestingly, we quantitatively demonstrated that compared with APOBEC3G, the antiviral activity of APOBEC3F was widely distributed but skewed toward lower activity, although their mean values were similar. We concluded that APOBEC3G markedly and robustly restricted the initial stages of viral growth in vivo . This is the first report to quantitatively elucidate how APOBEC3F and APOBEC3G differ in their anti-HIV-1 modes in vivo.